Honourable intentions?
1 online resource (xiii, 222 pages)
Keywords: "Honourable Intentions? compares the significance and strategic use of ideas of honour in two colonial societies, the Cape Colony and the early British settlements in Australia, between 1750 and 1850. In both regions swirled a free, and often transient, population of emigrants and sojourners, sailors and soldiers, merchants and traders, slaves and convicts, all with diverse backgrounds and transnational experiences. The mobile populations of colonial societies brought together cultures that held disparate, even contradictory, codes of honour and during these times of flux, concepts of honour and status were radically reconstructed"--Provided by publisher.